(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
A year round agronomical trial was conducted on station (Bangladesh Livestock Research Institute) to investigate the impact of seasonal variations on biomass production of Moringa oleifera at different fertilizer doses in Bangladesh. A 6×3 factorial arrangement in a completely randomized design (CRD) was applied on 20m×12m =240 m2 size plot, established in 2006 with a plant density of 13,500/hectare, was equally divided into 18 sub-plots and randomly grouped into three; 6 plots was treated as control, 6 plots was treated as medium with medium doses of fertilizer and rest 6 was treated as high fertilizer dose with the ratio of N.P.K was 90:30:15 and 160:60:40 kg/ha, respectively. The obtained result revealed that, the summer was the best season and autumn, monsoon and spring was also favorable for getting maximum yield of Moringa oleifera with ambient temperature ranges 27-320C and fertilization dose N:P:K= 90:30:15 is suitable for optimum moringa production and chemical composition of moringa varied with season and slightly with fertilization.